Genotypes of Epstein–Barr virus (EBV1/EBV2) in individuals with infectious mononucleosis in the metropolitan area of Belém, Brazil, between 2005 and 2016 - Monteiro,Talita Antonia Furtado (2020)
Abstract Two types of Epstein Barr virus (EBV1/EBV2) have been shown to infect humans. Although their genomes are similar, the regions containing the EBNA genes differ. This study aimed to characterize the EBV genotypes of infectious mononucleosis (IM) cases in the metropolitan region of Belém, Brazil, from 2005 to 2016. A total of 8295 suspected cases with symptoms/signs of IM were investigated by infectious disease physicians at Evandro Chagas Institute, Health Care Service, from January 2005 to December 2016. Out of the total, 1645 (19.8%) samples had positive results for EBV by enzyme immunoassay and 251 (15.3%) were submitted to polymerase chain reaction (PCR) technique, using the EBNA3C region, in order to determine the type of EBV. Biochemical testing involving aspartate aminotransferase, alanine aminotransferase and gamma-glutamyl transferase were also performed. EBV type was identified by PCR in 30.3% (76/251) of individuals; of those, 71.1% (54/76) were classified as EBV1, 17.1% (13/76) as EBV2, and 11.8% (9/76) as EBV1+EBV2. The main symptoms/signs observed with EBV1 infection were cervical lymphadenopathy (64.8%, 35/54), fever (63%, 34/54), headache (20.4%, 11/54), arthralgia (20.4%, 11/54), and exanthema (18.5%, 10/54). EBV2 infection was detected in all but two age groups, with an average age of 24 years. The most common signs/symptoms of EBV2 were fever (76.9%, 10/13), average duration of 18 days, and lymphadenopathy (69.2%, 9/13). In contrast, EBV1+EBV2 coinfections were more frequent in those aged five years or less (20.0%, 2/10). The symptoms of EBV1+EBV2 coinfection included fever (66.7%, 6/9), and cervical lymphadenopathy and headache (33.3%, 3/9) each. The mean values of hepatic enzymes according to type of EBV was significantly different (p<0.05) in those EBV1 infected over 14 years of age. Thus, this pioneering study, using molecular methods, identified the EBV genotypes in 30.3% of the samples, with circulation of EBV1, EBV2, and EBV1+EBV2 co-infection in cases of infectious mononucleosis in the northern region of Brazil.